Australian children undergoing selective dorsal rhizotomy: protocol for a national registry of multidimensional outcomes. Issue 4 (1st May 2019) - Lewis, Jennifer; Bear, Natasha; Baker, Felicity; Fowler, Adam; Lee, Olivia; McLennan, Kim; Richardson, Emma; Scheinberg, Adam; Smith, Nadine; Thomason, Pam; Tidemann, Andrew; Wynter, Meredith; et al.
Abstract : Introduction: Selective dorsal rhizotomy (SDR) is a neurosurgical intervention intended to permanently reduce spasticity in the lower limbs and improve mobility in selected children with cerebral palsy (CP). Despite SDR having been performed worldwide for the past 30 years, there is moderate quality of evidence that SDR is effective in reducing spasticity with low to very low evidence of its effectiveness in improving gait, function and participation, using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) system. Published studies have described outcomes for groups that differ in selection, surgical technique and postoperative rehabilitation making it difficult for clinicians to use this information to advise families on best management. There is substantial community interest in SDR. A small number of children with CP undergo SDR in Australia each year and some families seek the intervention at international sites. Capturing clinical outcomes and adverse event (AE) data for Australian children undergoing SDR will provide clinicians with information to help guide families considering SDR. Methods and analysis: The Australian SDR Research Registry is a national registry of multidimensional outcomes for Australian children undergoing SDR in an Australian or overseas centre. Data will be collected for up to 10 years following the surgery, to include surgery and admission details, surgical and long-term AEs, and outcome measures across the body structure and functions, activity and participation domains of the International Classification of Functioning, Disability and Health. Data will be collected at baseline, during inpatient admission and at 1, 2, 5 and 10 years post. The aim of collecting these data is to improve understanding of short-, medium- and long-term outcomes and adverse effects of the intervention. Ethics and dissemination: This study was approved by the individual Human Research and Ethics committees at the five Australian tertiary hospitals involved. Results will be disseminated via peer-reviewed publications and conference presentations. Trial registration number: ACTRN12618000985280; Pre-results.